Xanthogranulomatous oophoritis mimicking a dermoid cyst with ovarian torsion: A case report and review of the literature - Carrie A. Sibbald; Laura G. Cooney; Ross J. Molot; Daniel L. Pellicer (Elsevier, 2024)
Xanthogranulomatous oophoritis (XO) is a rare pseudotumor representing a destructive chronic inflammatory process often mistaken for malignancy or tubo-ovarian abscess. Xanthogranulomatous inflammation is most commonly seen in the kidneys and gallbladder and very rarely affects the genitourinary system. Definitive treatment is with surgical removal of affected tissue.This report presents the case of a 42-year-old woman with an 8 cm complex right adnexal cyst concerning for a dermoid cyst presenting with intermittent torsion. Final pathology after right salpingo-oophorectomy demonstrated xanthogranulomatous oophoritis.This case is of clinical significance for distinguishing the condition from common benign pathology or cancer since the recommended surgical procedure is different than for a dermoid cyst or malignancy. Correct identification of the condition is crucial for appropriate treatment and to avoid unnecessary morbid procedures if the mass is mistaken for malignancy or future repeat surgery if mistaken for a dermoid cyst or other common benign condition. This case documents the presentation of xanthogranulomatous oophoritis masquerading as a dermoid cyst for a condition with very few reported cases worldwide.